Eksplorasi Etnomatematika Museum Islam Indonesia Kiai Haji Hasyim Asy'ari Melalui Media Microsoft Powerpoint Berbasis Visual Basic Materi Teorema Pythagoras - fitroh; Hari Wahyuni, Isti; Febi Rosyadi, Cintya; Soleh, Rahmat; Rodliyah, Iesyah (Cartesian: Jurnal Pendidikan Matematika, 2025)
This study aims to describe the influence of ethnomathematics exploration at the Indonesian Islamic Museum K.H. Hasyim Asy'ari through visual basic-based Microsoft PowerPoint material on the Pythagorean theorem on student learning outcomes. This research is a quasi-experimental research using quantitative methods. The population is grade 8 students at SMPN 2 Jombang with a sample of 32 students in VIII-I. Data collection techniques using the test method. The data analysis technique uses inferential statistics that hypothesis test by using t-test to determine the influence of the exploration of the Indonesian Islamic Museum K.H. Hasyim Asy'ari with visual basic based Microsoft PowerPoint on learning outcomes. Based on the data analysis that has been carried out, it concluded that exploring the ethnomathematics of the Indonesian Islamic Museum K.H. Hasyim Asy'ari through visual basic-based Microsoft PowerPoint has a significant influence on student learning outcomes on the Pythagorean theorem topic.